2018
DOI: 10.3390/catal8110505
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Glycerol Using 3% H2O2 Catalyzed by Supported Nano-Au Catalysts

Abstract: A series of transition metal oxides or mixed oxides supported nano-Au catalysts were prepared for the selective oxidation of glycerol to glyceric acid using 3% H2O2. It was found that the composition and structure of supports significantly influenced the catalytic performance of catalysts. The mesoporous trimetal mixed oxide (CuNiAlO) supported nano-Au catalysts were more active in comparison with the others. In the present catalytic system, the highest glycerol conversion was 90.5%, while the selectivity of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Previous publications had reported that a small amount of H 2 O 2 was generated during alcohol oxidation due to the codissociation of O 2 and H 2 O. ,, We also noticed that direct addition of H 2 O 2 to improve oxidation of alcohols might generate explosive hazards. , However, the presence of water in H 2 O 2 (only 6.4 ppm) and the alcohol system will not lead to the formation of such hazards during EG conversion, which has been demonstrated in existing literature works. , …”
Section: Results and Discussionsupporting
confidence: 57%
“…Previous publications had reported that a small amount of H 2 O 2 was generated during alcohol oxidation due to the codissociation of O 2 and H 2 O. ,, We also noticed that direct addition of H 2 O 2 to improve oxidation of alcohols might generate explosive hazards. , However, the presence of water in H 2 O 2 (only 6.4 ppm) and the alcohol system will not lead to the formation of such hazards during EG conversion, which has been demonstrated in existing literature works. , …”
Section: Results and Discussionsupporting
confidence: 57%
“…In our previous report, we had discussed the mechanism of the glycerol oxidation reaction with 3% H 2 O 2 used as oxidant over Au/CuNiAlO . And a possible pathway for the oxidation of hydroxyl groups of primary alcohols in glycerol was proposed.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, it was observed a low conversion combined with a high selectivity or high conversion together with low selectivity. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Recently, Liu et al 40 reported the photoelectrochemical oxidation of 1,3-DHA directly from glycerol using nanoporous BiVO 4 , with high conversion and selectivity of 51%. However, side products such as glyceric acid, formic acid, glycolic acid, CO 2 , CO and H 2 O 2 and O 2 were observed.…”
Section: Expeditious Syntheses To Pharmochemicals 13-dihydroxyacetonmentioning
confidence: 99%